Islamisation in modern sciences: the way forward - Abdelaziz, Berghout (Kulliyyah of Science, IIUM, 2011)
This article provides an important framework for the development of Islamisation in general and Islamisation in sciences in particular. Islamisation as a scientific activity and process that takes place in a university context requires more than conceptualization and theorization. It demands strategisation, planning, implementation and evaluation. Hence, whatever is our conceptualisation of Islamisation the important message is what value or impact that may be added or created from this scientific activity. This article used textual analysis to introduce the concept of Islamisation and Islamisation in science stressing the need for more in-depth articulation of the activity from epistemological, methodological and education perspective. The article concludes that there is a need to enhance science education from an Islamic perspective so as to create a conducive environment for the development of Islamisation activities. Furthermore, the Muslim mind needs to engage in serious intellectual efforts to develop an Islamic epistemology and methodology for the development of scientific thinking and its applications in various disciplines.